2018
DOI: 10.1519/jsc.0000000000002493
|View full text |Cite
|
Sign up to set email alerts
|

Self-selected vs. Fixed Repetition Duration: Effects on Number of Repetitions and Muscle Activation in Resistance-Trained Men

Abstract: Nóbrega, SR, Barroso, R, Ugrinowitsch, C, da Costa, JLF, Alvarez, IF, Barcelos, C, and Libardi, CA. Self-selected vs. fixed repetition duration: effects on number of repetitions and muscle activation in resistance-trained men. J Strength Cond Res 32(9): 2419-2424, 2018-The aim of this study was to compare the effects of self-selected and fixed repetition duration (RD) on resistance exercise (RE) volume, muscle activation, and time under tension (TUT) per repetition and per session. Twelve resistance-trained me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
2
14
0
1
Order By: Relevance
“…In our study, we observed increases between 10-14% in maximal strength and 7-10% in muscle hypertrophy after 8 weeks, which is in line with a previous study also performed with untrained subjects (Ahtiainen et al, 2016). Additionally, we demonstrated that SELF results in greater number of repetitions per session and VL, which was also observed in a previous study from our laboratory (Nobrega et al, 2018a). Nevertheless, the increase in muscle strength and hypertrophy was similar to the RT protocols with lower volume (CON and SELF-EV), contradicting our initial hypothesis.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In our study, we observed increases between 10-14% in maximal strength and 7-10% in muscle hypertrophy after 8 weeks, which is in line with a previous study also performed with untrained subjects (Ahtiainen et al, 2016). Additionally, we demonstrated that SELF results in greater number of repetitions per session and VL, which was also observed in a previous study from our laboratory (Nobrega et al, 2018a). Nevertheless, the increase in muscle strength and hypertrophy was similar to the RT protocols with lower volume (CON and SELF-EV), contradicting our initial hypothesis.…”
Section: Discussionsupporting
confidence: 92%
“…Fifth: Unfortunately, the TUT per repetition throughout the set was not controlled. However, a study from our laboratory used an electrogoniometer to check the variation of TUT within the same set during SELF and CON protocols (Nobrega et al, 2018a). The results showed that TUT per repetition in the SELF protocol increased throughout the sets, possibly due to accumulated fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, researchers have attempted to alter the time parameters to improve hypertrophy and strength through increased ECC muscle tension via increased muscle activation or by increasing the time under tension [76][77][78]. Evidence has been mixed on the effects of extended durations on these performance metrics with some studies showing positive outcomes [77,78], but most showing no favorable outcomes [72,73,[79][80][81][82][83].…”
Section: Tempo Eccentric Trainingmentioning
confidence: 99%